2022
DOI: 10.1002/sd.2312
|View full text |Cite
|
Sign up to set email alerts
|

The barriers and drivers of environmental management accounting practices' adoption in developed and developing countries for sustainable development

Abstract: Barriers and drivers of environmental management accounting practices' (EMAPs) adoption were compared between developed and developing countries. This may assist to promote adoption of EMAPs by targeting and overcoming applicable barriers while promoting drivers that are specific to their circumstances, leading to sustainable development ultimately. Methodology: A qualitative, six-step systematic literature review (SLR) using ATLAS.ti 8 were employed. Four interdependent theories (institutional, contingency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
0
8
1
2
Order By: Relevance
“…EMA has become an essential component in the decision-making process in management accounting, particularly within the complex SCMSs that result from many forces, including globalisation, recognition of dimensions of sustainability, and cost-effective transportation channels [33]. While the link between EMA and sustainable supply chain management continued to receive academic attention in the past decades [34], progress in implementing EMAPs in developing countries, particularly Africa, continues to gain momentum, with many scholars showing interest [17,20,22].…”
Section: Background On the Need For Emaps In The Supply Chain Managem...mentioning
confidence: 99%
See 2 more Smart Citations
“…EMA has become an essential component in the decision-making process in management accounting, particularly within the complex SCMSs that result from many forces, including globalisation, recognition of dimensions of sustainability, and cost-effective transportation channels [33]. While the link between EMA and sustainable supply chain management continued to receive academic attention in the past decades [34], progress in implementing EMAPs in developing countries, particularly Africa, continues to gain momentum, with many scholars showing interest [17,20,22].…”
Section: Background On the Need For Emaps In The Supply Chain Managem...mentioning
confidence: 99%
“…The association between EMA and supply chain management has created a debate in the manufacturing sector, with many studies alluding to the fact that EMAPs improve environmental and financial performance [35,36]. However, several studies have identified barriers to implementing EMAPs in general [2,17]. According to [6], a systematic review of barriers to adopting EMA in small Chinese companies identified a lack of regulatory pressures and fewer expectations from the various stakeholders as barriers.…”
Section: Background On the Need For Emaps In The Supply Chain Managem...mentioning
confidence: 99%
See 1 more Smart Citation
“…İşletmelerin çevresel stratejileri benimsemeleri konusu üzerinde etkili olan faktörler literatürde; durumsallık teorisi, paydaş teorisi, meşruiyet teorisi ve kurumsal teori gibi farklı teorilerle incelenmiştir. Durumsallık teorisi, muhasebe uygulamalarının benimsenmesinin işletmenin faaliyet gösterdiği benzersiz koşullara bağlı olduğunu (van Der Poll, 2022), paydaş teorisi, işletmenin başarısının paydaşları ile olan ilişkisini yönetme yeteneğine bağlı olduğunu (Marshall vd. 2010), meşruiyet teorisi, işletmelerin faaliyetlerinin toplumdaki sosyal normlara ve değerlere uygun olması gerektiğini (Agustia, 2020) ifade eder.…”
unclassified
“…Kurumsal teoriye göre, örgütsel davranışlar ve uygulamalar, yasalar, değerler, kültürler, ortak bilişler, normlar ve sosyal beklentiler gibi dış çevre ve kurumsal çevreden büyük ölçüde etkilenir (Wang vd., 2019). Kurumsal teori, organizasyonun ve çalışanlarının uygulamalarını, eylemlerini, yapısını ve davranışlarını şekillendirmede izomorfizm 1 (eşbiçimlilik 2 ) adı verilen bir kavram aracılığıyla faaliyet gösteren dış kurumsal güçlerin rolünü ele alır (van Der Poll, 2022). Kurumsal teoriye göre işletmeler; hükümet, yasalar vb.…”
unclassified